Examining the Effects of Oil Price Long Memory and Exchange Rate Long Memory on Stock Market Behavior in Nigeria - Lawal, Adedoyin Isola; Dahunsi, Samuel Olatunde; Babajide, Abiola Ayopo; Asaleye, Abiola John; Iseolorunkanmi, Joseph Ojo; Inegbedion, Henry; Manasseh, Charles O.; Lawal-Adedoyin, Bukola, B. (International Journal of Energy Economics and Policy, 2020)
The study examined the effect oil price long memory and exchange rate long memory on Nigeria’s stock. We have used ARMA estimating techniques to assess whether one or both variables exert impact on the stock market in Nigeria. Our result shows that long memory stock price is driven by a long memory of the exchange rate and long stock of the oil price. We therefore recommend that policymakers pursue policies aimed at stabilizing, on the one hand, the exchange rate regime and ensuring the economy has a position in net oil exportations. We also recommend the development of portfolio strategies by market practitioners so that long-term memory in exchange rates as well as in oil pricing are considered when making investment decisions. Keywords: Exchange rate, oil prices, Share prices, long memory, ARMA JEL Classifications: G15, Q43, C58, O40 DOI: https://doi.org/10.32479/ijeep.9643